Metallographic and Mechanical Studies of a Cast Heat-Resisting Alloy - Aichaoui, M.; Hadji, A. (Металлофизика и новейшие технологии, 2017)
A heat-resistant steel tube from an ammonia plant made of modified HP40 steel that failed after short-term service is studied for damage mechanism. The assessment of material degradation is carried out using optical microscopy, scanning electron microscopy in combination with energy dispersive spectroscopy analysis, x-ray diffraction analysis, and mechanical tests. Results show that precipitation of the chromium-rich carbides induces the coalescence of grain boundaries. Significant growth and poor distribution of secondary carbides are also noticed through the matrix, which lead to a reduction of material ductility even after a short-term service. The main cause of failure appears to be damaged catalyst. Such a problem can cause a rise in temperature leading to localized overheating in the lower part of the tube. Overheating is primarily responsible for significant degradation in microstructure, creep strength, and mechanical properties of the tube.